Regional goverment synergy in handling people with Mental Disorders (ODGJ) in Nagan Raya Regency - Zamharira, Cut; Muazzinah, Muazzinah; Maqfirah, Syarifah Rizqa; Maqfrah, Tia (Jurnal Geuthèë: Penelitian Multidisiplin, 2024)
The number of people with mental disorders in Nagan Raya Regency reached 367 cases as  of August 2022 with various causes including schizophenia, depression, domestic violences and drug abuse.  This paper aim to examine the handing carried out based on the synergy of the Health Service and Community Health Centers which is supported by other communities such as the sub district head, gampong officials and local residents in hading ODGJ  cases, in order to reduce the number of ODGJ  in Nagan Raya Regency.  This research  uses four indicators of synergy according  to Doctroff, namely; effective communication, researchers detail the information obtained to answer the problem of this research.  Through the four indicators that have been tested, the results of this research show that there has been synergy between the Health Service and the Nagan Raya Regency Puskesmas inhandling people with mental disorders.